Administrasi Guru Dan Kegiatan Belajar Mengajar - Meti Fatimah; Muhammad Ilyas (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
Teacher administration is an important element in the implementation of effective and efficient education. This administration covers various aspects, including planning, implementation, evaluation, and management of educational resources. In the context of teaching and learning activities, teacher administration plays a role in ensuring that the learning process runs smoothly, is structured, and in accordance with the established curriculum. Teacher administration involves arranging lesson schedules, managing classes, monitoring student progress, and preparing and implementing learning programs. In addition, teacher administration is also related to the development of teacher professionalism through training and workshops aimed at improving the competence and quality of teaching. Effective teaching and learning activities depend not only on the academic abilities of teachers, but also on their ability to manage administration well. With well-organized administration, teachers can focus more on the teaching process, create a conducive learning environment, and meet the individual needs of students. This study aims to explore the relationship between teacher administration and the effectiveness of teaching and learning activities in schools. The results of the study are expected to provide new insights for the development of better education management strategies, as well as improving the quality of education at various levels. Abstrak Administrasi guru merupakan elemen penting dalam penyelenggaraan pendidikan yang efektif dan efisien. Administrasi ini mencakup berbagai aspek, termasuk perencanaan, pelaksanaan, evaluasi, dan pengelolaan sumber daya pendidikan. Dalam konteks kegiatan belajar mengajar, administrasi guru berperan dalam memastikan bahwa proses pembelajaran berjalan dengan lancar, terstruktur, dan sesuai dengan kurikulum yang telah ditetapkan. Administrasi guru melibatkan pengaturan jadwal pelajaran, pengelolaan kelas, pemantauan perkembangan siswa, serta penyusunan dan pelaksanaan program pembelajaran. Selain itu, administrasi guru juga berkaitan dengan pengembangan profesionalisme guru melalui pelatihan dan workshop yang bertujuan untuk meningkatkan kompetensi dan kualitas pengajaran. Kegiatan belajar mengajar yang efektif tidak hanya bergantung pada kemampuan akademis guru, tetapi juga pada kemampuan mereka dalam mengelola administrasi dengan baik. Dengan administrasi yang tertata rapi, guru dapat lebih fokus pada proses pengajaran, menciptakan lingkungan belajar yang kondusif, dan memenuhi kebutuhan individual siswa. Penelitian ini bertujuan untuk mengeksplorasi hubungan antara administrasi guru dan efektivitas kegiatan belajar mengajar di sekolah. Hasil penelitian diharapkan dapat memberikan wawasan baru bagi pengembangan strategi pengelolaan pendidikan yang lebih baik, serta meningkatkan kualitas pendidikan di berbagai jenjang.